2014
DOI: 10.1002/jnr.23344
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ion influx in microglial cells: Physiological and therapeutic significance

Abstract: Microglial cells, the immunocompetent cells of the central nervous system (CNS), exhibit a resting phenotype under healthy conditions. In response to injury, however, they transform into an activated state, which is a hallmark feature of many CNS diseases. Factors or agents released from the neurons, blood vessels, and/or astrocytes could activate these cells, leading to their functional and structural modifications. Microglial cells are well equipped to sense environmental changes within the brain under both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 130 publications
2
26
0
Order By: Relevance
“…limited to neurons and myocytes), with [Ca 2+ ] in nonexcitable cells being controlled by other mechanisms such as store-operated Ca 2+ -entry. However, there is increasing evidence that VGCCs are in fact expressed and functional in many non-excitable cells [69], including in some lymphocytes [70,71] and in glia [72][73][74]. It therefore cannot be excluded that VGCCs have a role in [Ca 2+ ] regulation in many cell types, although this would seem likely to be at most a minor contribution to the results reported here, especially since VGCCs are not expressed in platelets or their megakaryocyte precursors [75].…”
Section: Discussionmentioning
confidence: 71%
“…limited to neurons and myocytes), with [Ca 2+ ] in nonexcitable cells being controlled by other mechanisms such as store-operated Ca 2+ -entry. However, there is increasing evidence that VGCCs are in fact expressed and functional in many non-excitable cells [69], including in some lymphocytes [70,71] and in glia [72][73][74]. It therefore cannot be excluded that VGCCs have a role in [Ca 2+ ] regulation in many cell types, although this would seem likely to be at most a minor contribution to the results reported here, especially since VGCCs are not expressed in platelets or their megakaryocyte precursors [75].…”
Section: Discussionmentioning
confidence: 71%
“…Homeostatic microglia are considered to be in a sensing state 15 , equipped to detect environmental changes in order to respond to a variety of stimuli. At the center of this transformation is identification of several surface channels and receptors that are critical for entry of calcium ions 16,17 . Thus, PWK are predicted to be a novel strain in which to understand differences related to this process.…”
Section: Resultsmentioning
confidence: 99%
“…PLCγ2 hydrolyzes the membrane phospholipid PIP 2 to form the secondary messenger inositol triphosphate (IP 3 ), which promotes the release of calcium into the cytoplasm. Functional alterations of PLCγ2 impact the IP 3 /Ca 2+ signaling pathway, found determinant for microglial properties [68] . Of interest, Tau misfolding could also impact IP 3 production, as it was shown that physiological Tau exerts a tonic inhibition on the phosphatase PTEN reducing the formation of PIP2 [14] .…”
Section: Ad Tauopathies and Inflammation: Genetic Evidencesmentioning
confidence: 99%